(untitled) (Journal of Pharmaceutical Negative Results, 2023)
OBJECTIVES High-intensity interval training is a popular form of interval training. A study found the impact of high-intensity interval training on resting pulse rate and blood pressure among football players' understudies. METHODS To Achieve the justification behind a focus on 30 football players from GTN College of Arts and Science, Madurai Kamaraj University, Madurai, Tamil Nadu, India. The age ranged divided into 18 to 25 years. They were randomly divided and assigned into two groups of fifteen each as the experimental group (high-intensity interval training) 1(n=15) and control group 1 (n=15). The data were collected pre and post of the training period of 8 weeks, and the data collected from the subjects were statistically analysed f ration to find out significant improvement, if any, at a 0.05 level of confidence. RESULTS The obtained resting pulse rate test for HIIT and CG F-Ratio regard 5.96*; the procured systolic pressure later test for HIIT and CNG F-Ratio regard 3.65*. The procured diastolic pressure later test for HIIT, and CNG F-Ratio regard 4.89* seen as higher than the fundamental worth 3.23 was on an elementary level more imperative than the table worth 3.23 DF 1 and 28. CONCLUSION The results of the resting pulse rate, systolic and diastolic pressure improved significantly due to the impact of high-intensity interval training with the limitations of ( diet, climate, lifestyle) status, and previous training; the result of the present study coincides with the findings of the investigation done by different experts in the field of sports sciences. High-intensity interval training significantly improved college football players' resting pulse rate and systolic and diastolic pressure.